The curriculum framework for institutional internalisation of criminology and forensics studies at University of Limpopo, South Africa: A scoping review - Maluleke, W. (South African Journal of Higher Education, 2024)
Studies offering curriculum framework for institutional internalisation of criminology and forensics studies and Work-Integrated Learning (WIL) within the Criminal Justice System (CJS) are scarce. This article gives a scoping review of these concepts, which are currently presented separately, as they are from distant study fields. As a result, the objective of this article is to establish the current link between criminology and forensic studies to enhance the South African CJS and Higher Education Institutions (HEIs) curriculum frameworks, while integrating theory and practice. This qualitative scoping review was supported by the adapted version of methodology framework by Arksey, Hilary and O’Malley, Lisa of 2005 to search for approximately 9 031 relevant studies from fundamental databases and 139 000 internet sources focusing on South African context and other international countries. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was used for data analysis, coupled with the inductive Thematic Content Analysis (TCA). This article confirmed that combining forensic criminology features could transform the South African CJS and HEIs offerings. For recommendations, the Qualifications Board should expedite the registration of forensic criminology as a profession consisting of professional qualification, guided by ethical and disciplinary rules. Overall, limited prioritisations, slow registration process to a “Scientific Board” and advancement of this discipline negatively affect immediate responses to achieve the WIL. The knowledge, attitudes, skills and values gained during participating in the South African Future Professors Programme (FPP) Phase 2 Cohort 1 2022‒2023 offered contributions to the field of professorship thereof.